Molecule counts in localization microscopy with organic fluorophores - Karathanasis, Christos; Heilemann, Mike (ChemPhysChem, 2017)
Single-molecule localization microscopy (SMLM) can be used to count fluorescently labeled molecules even when they are not individually resolved. We demonstrate SMLM molecule counting for nucleic acids labeled with the organic fluorophore Alexa Fluor 647 and imaged under photoswitching conditions. From the observed distributions of the number of fluorophore blinking events, we extract the number of fluorophores per spot using a statistical model. We validate the molecule counting method for single Alexa Fluor 647 fluorophores, and for trimers of Alexa Fluor 647 constructed on a DNA origami structure. This simple counting strategy enables quantitative super-resolution imaging with organic fluorophores.